Exploring aspects of participation at South African community radio stations. - Jean Michel, Lionel (My University, 2016)
Community radio is radio that has been established to serve a particular community. Girard (1992) maintains that community radio must fulfil the expectations of the sector as a participatory medium. This research paper explores aspects of participation within community radio, specifically how it plays out through radio programming, new media, volunteerism and community outreach projects. New media technologies have revolutionised participation by giving rise to platforms that have empowered and transformed what were once passive content consumers into audiences who have become significant role players. These audiences have become key role players in deciding what needs to be transmitted to the community via their local community radio, setting the tone for discussions, information dissemination and conversations that affect the local community.